Assessment of adherence to the national stress ulcer prophylaxis guidelines: A cross-sectional analysis - Shaden S Alhujilan; Mustafa S Saeed; Abdullah Abdulaziz Alalwan (Elsevier, 2023)
Background: Clinical guidelines support the use of stress ulcer prophylaxis (SUP) in patients at risk of gastrointestinal (GI) bleeding such as those with coagulopathy, renal replacement therapy, and mechanical ventilation. Despite the observed benefits of SUP, its overuse has been highly associated with serious adverse effects. Objective: To assess the adherence to the national SUP guidelines in a tertiary hospital in Saudi Arabia. Methods: A cross-sectional study was conducted using electronic health records at King Fahad Specialist Hospital (KFSH), Buraydah, Saudi Arabia. We collected the data from January 1st to December 31st, 2020. Adult patients aged 18 and older who received SUP prescriptions were included. Descriptive analysis was performed to assess the adherence to the guidelines and to explore the factors associated with SUP use in a hospital-based setting. Results: A total of 424 patients were enrolled in this study. The median age of patients was 55.2 years old. Only 54% of patients were candidates for SUP. Internal medicine and surgery wards ranked the highest in prescribing SUP at 34.2% and 30.4%, respectively. The most common major criterion to start SUP was the concomitant use of two or more of these medications (anticoagulants, aspirin, non-steroidal anti-inflammatory drugs (NSAIDs), corticosteroids, and antidepressants) followed by using NSAIDs or corticosteroids by older adult patients aged (≥65 years) or have GI bleeding history at 43.2% and 21.5%, respectively. Conclusion: The observed overuse of anti-ulcer drugs (AUD) indicates a need for greater adherence to SUP guidelines. Areas of improvement can be implemented to ensure appropriate adherence to SUP guidelines to control the costs and avoid unnecessary anti-ulcer-related adverse effects.